Prevailing Food Intake, Physical Activity and Health Beliefs in a Rural Agricultural Community in the Philippines: Factors to Consider Prior to a Diabetes Prevention Program - Sandoval, Mark Anthony; Paz-Pacheco, Elizabeth; Canete, Edwin; Patal, Perpetua; Cating-Cabral, Monica Therese; Lantion-Ang, Frances Lina; Paterno, Elizabeth; Juban+, Noel; Jimeno, Cecilia (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Objective. A diabetes prevention program is being proposed in the rural agricultural town of San Juan, Batangas, Philippines. This study aims to determine the prevailing level of food intake, physical activity, and health beliefs prior to any intervention. Methodology. Adults were recruited via random sampling with proportional allocation. Interviews were done to determine food intake and physical activity. Small group discussions were held to determine prevailing health beliefs. Results. The average energy intake (1,547 kcal/d) is only 72% of the recommended values for Filipinos. Only 12% of the respondents achieved the recommended energy intake. Carbohydrates comprise a large part (71%) of calorie intake. A majority (91%) already have moderate to high levels of physical activity. There are prevailing health beliefs that need to be considered when dietary modifications and physical activity interventions are to be done. Conclusion. Internationally recommended diabetes prevention interventions such as reducing calorie intake and increasing physical activity may not be directly applicable here. We recommend that the features of a diabetes prevention program for this locale must include the following: 1) introduction of affordable plant sources of proteins; 2) decreasing the proportion of rice as a source of carbohydrates in the diet; 3) maintaining the level of physical activity; and 4) being sensitive to the prevailing health beliefs.